Liquid Biopsies: Photonic Technologies for Liquid Biopsies: Recent Advances and Open Research Challenges (Laser Photonics Rev. 15(1)/2021). Issue 1 (8th January 2021) - Dell'Olio, Francesco; Su, Judith; Huser, Thomas; Sottile, Virginie; Cortés‐Hernández, Luis Enrique; Alix‐Panabières, Catherine
Abstract : The emerging field of liquid biopsies could contribute to a paradigm shift in cancer diagnosis/treatment and the recent advances in photonics are supporting and enabling this process. In article number 2000255, Francesco Dell'Olio and co‐workers critically review the recent advances and open research challenges in the field of photonic technologies for liquid biopsies, discussing the most promising paths of improvement and the competing technologies.